Graphene oxide architectures prepared by molecular combing on hydrophilic-hydrophobic micropatterns - Wu, Jumiati (2014)
A novel graphene oxide (GO) architecture is fabricated on hydrophilic-hydrophobic patterned alkanethiol self-assembled monolayers on Au by molecular combing of GO sheets. With hydrazine reduction, the reduced GO architecture-based device is demonstrated to detect NO2 gas. This simple method shows the potential to control the shape, orientation and position of GO sheets over large areas.